An analysis on the suitability of selected newspaper material as a teaching resource in efl courses. - Hidalgo, Susana (2010)
The principal aim or goal of this research was to find out if newsprint is a useful resource to teach reading, grammar and vocabulary to students of different levels of English as a second language. With the purpose of obtaining the Bachelor´s Degree in Teaching English as a Foreign Language, Universidad Técnica Particular de Loja requested the students to carry out the research titled: An analysis of the suitability of selected newspaper material as a teaching resource in EFL courses.